2020
DOI: 10.1002/gea.21810
|View full text |Cite
|
Sign up to set email alerts
|

Cinnabar provenance of Chalcolithic red pigments in the Iberian Peninsula: A lead isotope study

Abstract: We report lead isotope data for cinnabar from three Chalcolithic settlements and several ore deposits in the Iberian Peninsula. Lead isotope ratios of cinnabar (vermilion) employed in one Bell Beaker grave at Humanejos (Madrid) plot in the field of the Almaden mining district. Cinnabar from the La Velilla dolmen (Palencia) also plots in the isotopic field of Almaden ores but is also comparable to the closer Miñera de Luna deposit in the Cantabrian Ranges. Cinnabar used in the dolmen of Montelirio (Seville) has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 49 publications
0
15
0
3
Order By: Relevance
“…Bands of cinnabar are present on a Pre-Pottery Neolithic B (ninth-eighth millennium BC) child skull at Tel Abu Hureira in Syria 31 and a woman’s skull at Çatalhöyük in Turkey, where cinnabar was used not only in burial contexts but also as pigment in wall paintings 32 . Almadén de la Plata (Ciudad Real) in central Spain is one of the largest natural sources of cinnabar in the world 33 , and analytical studies have demonstrated this site as one of the main sources of cinnabar present at other archaeological sites 34 . The exploitation and use of cinnabar as a pigment in Iberian prehistory is a well documented phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Bands of cinnabar are present on a Pre-Pottery Neolithic B (ninth-eighth millennium BC) child skull at Tel Abu Hureira in Syria 31 and a woman’s skull at Çatalhöyük in Turkey, where cinnabar was used not only in burial contexts but also as pigment in wall paintings 32 . Almadén de la Plata (Ciudad Real) in central Spain is one of the largest natural sources of cinnabar in the world 33 , and analytical studies have demonstrated this site as one of the main sources of cinnabar present at other archaeological sites 34 . The exploitation and use of cinnabar as a pigment in Iberian prehistory is a well documented phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] and Rodríguez et al . [ 73 ]. No permits were required for the analysis of geological samples.…”
Section: Methodsmentioning
confidence: 99%
“…In Minami et al (2013), the accuracy of the isotopic ratios was of 0.1-0.3% and 0.3-0.6% with 206 Pb and 204 Pb as the denominator, respectively 15 . Rodríguez et al (2020) prepared the sample through the following procedures (in order): preliminary digestion by HNO 3 (1st day), removal of supernatant and rinsing of the residue with H 2 O, digestion with HF (2nd day), removal of supernatant, rinsing of the residue with H 2 O and XRD, digestion with aqua regia (3rd day), evaporation to dryness, ion exchange in hydrobromic acid, lead elution by HCl. Measurements were made using a multicollector inductively coupled plasma mass spectrometer (MC-ICP-MS).…”
Section: The Provenance Of the Pigmentmentioning
confidence: 99%
“…andRodríguez et al (2020). Other data on cinnabar ores have been further provided byJébrak et al (2002), on recrystallised pyrite andHigueras et al (2005) on cinnabar.…”
mentioning
confidence: 99%